LITERATURE STUDY OF MODIFICATION SCALE MEDIA IN LEARNING MEASUREMENT CONCEPTS OF CHILDREN 5-6 YEARS OLD - Siti Rahmawati; Eka Cahya Maulidiyah (Universitas Sebelas Maret, 2020)
In the development of cognitive aspects one of the parts in it is mathematics. One concept in mathematics that is very close to children is the concept of measurement. However, learning in children is quite difficult for teachers to do. This is because the concept of measurement is one of the concepts in mathematics which is quite abstract if only taught without the existence of a learning medium as a tool in the learning process. Teaching the concept of measurement in kindergarten is still lacking in variety and tends to only use Child Worksheets (LKA) which directly or indirectly will seem very boring and seem monotonous. Therefore, it is necessary to have a new learning media in the process of learning the measurement concept that aims to make it easy for children to learn the measurement concept. This study aims to describe the use of the modified media scales in the learning of measurement concepts that are aimed at children aged 5-6 years. Indicators of measurement concepts related to the child's ability to understand the concept of measuring the weight of objects with the intended subject are early childhood with an age range of 5-6 years. This type of research is a literature review that is using literature studies in a scientific study relating to the variables in the study. Analysis techniques in research by analyzing some relevant research from related articles obtained, discovered, analyzed and concluded. The results of the data analysis concluded that the use of modified media scales in the learning process of measuring concepts can provide convenience for children in learning the measurement concepts.